WJEC GCSE religious studies unit 1 religion and philosophical themes - Clarke, Steve; White, Joy; Pawson, Ed (Dynamic learning, 2017)
Exam Board: WJEC Level: GCSE Subject: Religious Studies First Teaching: September 2016 First Exam: Summer 2018For the new Welsh specification for first teaching 2017 Stretch and challenge your students to achieve their full potential with learning materials that guide them through the new Unit 1 content and assessment requirements; developed by subject experts with examining experience and the leading Religious Studies publisher- Enables you to teach philosophical themes confidently with clear explanations of Christian, Muslim, Jewish and Buddhist beliefs and practices.- Motivates students to build and cement their knowledge and skills using a range of imaginative, innovative activities that support learning and revision.- Prepares students for examination with exam focus sections at the end of each unit that provide guidance on how to tackle questions.- Helps students of all abilities fulfil their potential and increase their understanding through clear, detailed explanations of the key content and concepts. WJEC GCSE Religious StudiesUnit 1 Religious Responses to Philosophical ThemesCovering:- Christianity- Islam- Judaism- Buddhism- Life and Death- Good and Evil